Pansteatitis in a cat - Faridah Noor ,; Chooi, Kum Fai (Persatuan Doktor Veterinar Malaysia, 1984)
A case of pansteatitis in a cat is described. The disease is rare or underdiagnosed. Common clinical signs are pyrexia, anorexia, lumbar and abdominal pain, and presence of subcutaneous lumps of fatty tissue. Cats fed a principally fish-based diet are especially at risk.